Suffering and prejudice: do negative emotions predict immigration concerns? - Sumit S. Deole; Yue Huang (Journal of Population Economics, 2024)
This paper examines the role of individuals' emotions in determining their concerns about international migration. For the empirical analysis, we exploit little-explored information in the German Socio-Economic Panel (SOEP) data on individuals' negative emotions, e.g., anger, fear, and sadness. We find that the frequency of experiencing negative emotions is positively associated with immigration concerns. Moreover, we show that the relationship varies across employment status, birth cohort, and social media usage. Our analysis also underscores the real-life consequence of emotions by demonstrating their positive association with support for far-right political parties among males, but not among females. Finally, we exploit the exogenous variation in negative emotions induced by the death of a parent to infer causality. Fixed effects regressions with instrumental variables exhibit a positive impact of negative emotions on immigration concerns among females, but no significant effects are found among males. Further investigation into channels driving these gender differences in results underscores gender differences in roles played by other concerns that often carry over to determine individuals' immigration concerns, e.g., concerns about international terrorism.
Keywords: D91; F22; P16; 330; Negative emotions; Immigration concerns; Bereavement